2003
DOI: 10.1097/01.olq.0000099160.26205.22
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Neisseria gonorrhoeae and Chlamydia trachomatis in Men Who Have Sex With Men at Male-Only Saunas

Abstract: The high prevalence rate of gonorrhea and chlamydia supports the concept of a screening program in Melbourne male-only saunas. The low participation rate has highlighted the need to consider alternative methods for making contact with men in the saunas or offering incentives to participate in future screening programs. Although anonymous participation encouraged participation for some men, future programs should attempt to obtain contact details for follow up of positive test results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 9 publications
4
62
0
Order By: Relevance
“…The three COBAS Amplicor-positive and omp1 PCR-negative anal samples all contained adequate amplifiable DNA and a lack of inhibitors, as shown by ␤-globin detection (14,21,22). It is most probable that these samples were not false positives, but rather contained bacterial levels that were below the detection level of the omp1 PCR assay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The three COBAS Amplicor-positive and omp1 PCR-negative anal samples all contained adequate amplifiable DNA and a lack of inhibitors, as shown by ␤-globin detection (14,21,22). It is most probable that these samples were not false positives, but rather contained bacterial levels that were below the detection level of the omp1 PCR assay.…”
Section: Discussionmentioning
confidence: 99%
“…Specimens were collected from men who participated in a screening program in male-only saunas in Melbourne, Australia (14). All specimens from this program were tested for C. trachomatis by COBAS Amplicor PCR (14).…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, these findings of a high incidence among men who have sex with men are consistent with the data reported by Lister et al, who found that participants attending a male-only sauna in Melbourne had a higher risk of infection if they had recently sought sexual health advice. 3 While the incidence rates are much lower for women, they indicate a level of unprotected sexual activity. This analysis can be repeated in subsequent years to monitor incidence over time.…”
Section: Gendermentioning
confidence: 99%
“…In Australia, asymptomatic urethral gonorrhoea among MSM is rare, and asymptomatic screening is therefore not recommended. 8 We requested clinicians to ask MSM fulfilling these criteria if they were willing to participate in the study. Informed consent was obtained from these clients and a questionnaire was distributed to them after the clinical consultation, during which specimens for Ng and Ct testing were collected.…”
Section: Study Populationmentioning
confidence: 99%
“…Although several recent studies have described the symptoms and clinical signs of rectal Ng and Ct on presentation, 1−7 it is unclear from these studies whether or not symptoms are reliable clinical indicators for Ng and Ct rectal infection as few studies have reported on anorectal symptoms in MSM with and without rectal Ng or Ct. 1,4,5 Relatively few MSM with Ng or Ct rectal infection have reported rectal symptoms in previous Melbourne studies. 8,9 The present study compares the symptoms of rectal Ng and Ct with MSM without rectal Ng and Ct at the Melbourne Sexual Health Centre (MSHC) and examines whether anorectal symptoms can be used as clinical correlates of rectal Ng and Ct. The study also compares anorectal symptoms reported during a clinical consultation compared with those elicited via a questionnaire.…”
Section: Introductionmentioning
confidence: 99%